Gathering and critically editing the Ittifaqat of Mzab - Daddi Addoun, Yacine (2025)
This panel brings together scholars and specialists to explore an Arabic and Berber (Amazigh) manuscript tradition, with a focus on codicology and cataloguing. It examines how these texts were created, circulated, and preserved, offering a glimpse into the morphological and paleographical strategies that allow us to learn about northwest Africa’s literary heritage. The panelists will collectively consider how we define the fields of Arabic and Amazigh manuscript studies through an interdisciplinary approach, challenging traditional binaries and exploring how Arab and Berber communities engaged with shared material practices over the centuries. Through this discussion, the panel aspires to generate new frameworks for understanding the historical and cultural significance and legacy of these sources.
Institution: Center for African Studies
Keywords: Droit coutumier – Mzab